Skin temperature increase after whole body postmortem magnetic resonance imaging. (December 2020) - Kobayashi, Tomoya; Shiotani, Seiji; Muranaka, Hiroyuki; Saitou, Hajime; Tashiro, Kazuya; Someya, Satoka; Yoshida, Masahiro; Kaga, Kazunori; Miyamoto, Katsumi; Hayakawa, Hideyuki; Homma, Kazuhiro
Highlights: 1.5 T whole body postmortem magnetic resonance (PMMR) imaging was taken for 1 h. The causes of skin temperature increase ( Tinc ) after PMMR imaging was investigated. Average specific absorption rates of PMMR imaging were within the safe range. Tinc is hardly influenced by radiofrequency heating but rather by room temperature. 1.5 T whole body PMMR imaging for 1 h does not significantly warm up a cadaver. Abstract: Purpose: To investigate causes for skin temperature increase after whole body postmortem magnetic resonance (PMMR) imaging. Material and methods: We performed PMMR imaging using a 1.5 T clinical scanner on 28 deceased human adults. The corpses were kept in cold storage at 4 ℃ before MRI and the scan room was maintained at 23 ℃. Skin temperatures of corpses before and after MRI were measured and average specific absorption rates (SAR) of the measured points were calculated. Results: Average skin temperature before and after PMMR imaging was 11.8 ± 5.8 ℃ and 15.0 ± 5.1 ℃, respectively. Average skin temperature increase was 3.2 ± 1.4 ℃, and whole-body average SAR in all sequences was 0.97 ± 0.94 W/kg. The skin temperature increase correlated significantly with the difference between the average initial skin temperature before PMMR imaging and the room temperature ( R 2  = 0.388, P  = 0.002), but did not correlate significantly with whole-body average SAR in all sequences ( R 2  = 0.032, P  = 0.662 > 0.05). Conclusion: The skin temperature increase during whole body PMMR imaging is more likely influenced by room temperature than by RF energy-induced heating effect. RF heating effect in PMMR imaging is minimal, and it appears to be no significant issue to conduct 1.5 T PMMR imaging prior to autopsy.